2005
DOI: 10.1002/jlcr.1012
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization and biological evaluation of99mTc(CO)3-labelled cyclic polyamines

Abstract: SummaryThree cyclic polyamines, namely 1,4,7-triazacyclononane, 1,4,7,10-tetraazacyclododecane (cyclen) and 1,4,8,11-tetraazacyclotetradecane (cyclam), were evaluated as potential ligands for complexation of a technetium(I) tricarbonyl core. They can be used as bifunctional chelating agents for labelling bioactive compounds. Each of the three ligands forms a positively charged technetium tricarbonyl complex in high yield but heating is required to promote complex formation. The charge of the 99m Tc(I)tricarbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Determination of the distribution coefficient was carried out by a shake flask method [31]. An aliquot (25 mL) of 99m Tc-5, 99m Tc-8 or 99m Tc-11A and 99m Tc-11B (185 kBq/mL) was added to a polypropylene tube (5 mL) (Sarstedt, Nümbrecht, Germany) containing 2 mL of 0.025 M sodium phosphate buffer pH 7.4 and 2 mL 1octanol.…”
Section: Log D 1àoctanol/phosphate Buffer Ph 74 Determinationmentioning
confidence: 99%
“…Determination of the distribution coefficient was carried out by a shake flask method [31]. An aliquot (25 mL) of 99m Tc-5, 99m Tc-8 or 99m Tc-11A and 99m Tc-11B (185 kBq/mL) was added to a polypropylene tube (5 mL) (Sarstedt, Nümbrecht, Germany) containing 2 mL of 0.025 M sodium phosphate buffer pH 7.4 and 2 mL 1octanol.…”
Section: Log D 1àoctanol/phosphate Buffer Ph 74 Determinationmentioning
confidence: 99%
“…NOTA and NODAGA chelators can accommodate various radiometals, most commonly the PET (positron emission tomography) radionuclides 68 Ga and 64 Cu, and result in hydrophilic complexes of good stability. Interestingly, TACN and its derivatives are capable of coordinating the fac -[M­(CO) 3 ] + core, leading to stable complexes in vitro and in vivo . The crystal structure of fac -[Re­(CO) 3 (TACN)] + revealed complexation via the (N,N,N) donor set in a distorted octahedral conformation with facial CO groups and formation of five-membered chelate rings . We published the first examples of [ 99m Tc]­[Tc­(CO) 3 (TACN)]-functionalized bombesin derivatives, which displayed high in vitro binding affinity for gastrin-releasing peptide receptors (GRPR) in prostate cancer cells (PC-3) .…”
Section: Introductionmentioning
confidence: 99%
“…These include NOTA and NODAGApolycarboxylate derivatives of 1,4,7-triazacyclononane which can coordinate to the fac-[M(CO) 3 ] + core, resulting in stable, hydrophilic complexes. 173,174 In 2018, Makris et al first explored [ 99m Tc] Tc/[ 186 Re]Re-tricarbonyl core with NOTA and NODAGA BFCs conjugated to sst 2 -ANT, the somatostatin receptor antagonist 4-NO 2 -Phe-c(DCys-Tyr-DTrp-Lys-Thr-Cys)-DTyr-NH 2 . 175 They were prepared in high radiochemical yields and biodistribution studies in healthy mice with the [ 99m Tc] Tc(CO) 3 (NODAGA)-peptide bioconjugate revealed outstanding pharmacokinetics, such as negligible non-specific organ uptake and rapid renal clearance after 1 hour.…”
Section: Rsc Medicinal Chemistry Reviewmentioning
confidence: 99%